1984
DOI: 10.1002/jso.2930250404
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of skin melanoma with regional node metastases (stage II)

Abstract: 566 stage-II melanoma patients treated at the National Cancer Institute of Milan, Italy, were analyzed to evaluate the prognosis. Among the criteria considered, four were significantly associated with survival when considered as single factors: growth pattern, levels of invasion, the number of involved lymph nodes, and the extent of metastatic growth. As regards growth pattern, the observed 5-year survival rates were 41.9% for superficial spreading melanoma and 20.5% for nodular melanoma (P = 10(-3)). As regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 9 publications
1
23
0
2
Order By: Relevance
“…The prognosis of stage Illb melanoma patients is poor (overall 5-year survival: 36%), particularly when mor than one node is histologically involved [9][10][11][12], showing the need for effective adjuvant therapy to improve DFS.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of stage Illb melanoma patients is poor (overall 5-year survival: 36%), particularly when mor than one node is histologically involved [9][10][11][12], showing the need for effective adjuvant therapy to improve DFS.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of these patients die of their disease within 2 years (Cascinelli et al, 1984), and the prospects are even worse for patients with distant metastases (AJCC stage IV). Even when surgical excision is feasible, the 2 year survival rates for these patients range only from 14 to 26% (Eton et al, 1998).…”
mentioning
confidence: 99%
“…Bevilacqua et al also found that the percentage of positive nodes was predictive of outcome in patients with melanoma metastatic to axillary nodes [8]. Further, the presence or absence of extranodal soft-tissue disease within the lymphadenectomy specimen has been found highly predictive outcome in melanoma [8,17,18].…”
Section: Biological Argumentsmentioning
confidence: 95%
“…These studies have shown that in patients with melanoma metastatic to regional nodes, tumor burden is a consistent and important predictor of outcome. The number of positive nodes has been shown to be a significant prognostic factor by univariate analysis in several studies [7][8][9][10] and by multivariate analysis in others [11][12][13][14][15][16][17]. Fiveyear survival has been found to decrease steadily as the number of positive lymph nodes increases [7][8][9][10][11][12][13][15][16][17][18].…”
Section: Biological Argumentsmentioning
confidence: 98%